Review Artikel: Target Aksi Obat Antiepilepsi Terhadap Reseptor Kanal Ion Natrium - Munir Alinu Mukti; Jekmal Malau; Saarah Hamidah Asmara Indratno; Shafira Intan Anggraini; Shinta Puspa Dwiyanti; Siti Nafisa; Siti Rohmah; Sofianti Hidayat (Jurnal Ilmiah Wahana Pendidikan, 2023)
Ion channels are selective pore complexing proteins. One of the ions that can be passed is sodium ion (Na+). Disturbances in the sodium channel (Na+) can be caused epilepsy disease. Epilepsy is a neurological condition characterized by recurrent seizures caused by brief disorders of electrical function in the brain. The purpose of this review is to determine the sodium ion channel receptor as a target for the action of antiepileptic drugs. The method used is based on a literature study. A total of 17 journals through the Google Scholar search engine, PubMed, ScienceDirect, and Microbiology Textbook were applied. The result of analysis using the entire reference showed that the mechanism of action of anti-epileptic drugs is specific for inhibition of the Na+ which is known that depend on the action potential. Examples of drugs are Phenytoin, Carbamazepine, & Lamotrigine. Phenytoin works by binding and blocking active sodium ion channels to reduce the number of open channels along the axon/cell body so that it will inhibit high-frequency release by slowing channel replacement and blocking continuous sodium currents. In addition, Carbamazepine works by blocking Na+ channels, so that there is no influx/entry of Na+ into the nerve cells. It will be effect that excessive depolarization does not occur and seizures can be stopped immediately. Another drug, Lamotrigine is similar to Phenytoin and Carbamazepine. The mechanism is voltage-dependent sodium channel conductance, stabilizing the nerve membrane thereby modulating the release of presynaptic excitatory neurotransmitters and inhibiting presynaptic glutamate.